2017
DOI: 10.56431/p-845mhd
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molarity on Structural and Optical Properties of Chemically Deposited Nanocrystalline PbS Thin Film

Abstract: Thin films of PbS were deposited by chemical bath deposition (CBD) method under various molarities using lead acetate as Pb2+ ion source, thiourea as S2- ion source and ammonia as complexing agent at a fixed pH value of 9 under bath temperature of 333 K. Four different molarities of PbS thin films were prepared. The as-prepared films were characterized by using X-ray diffraction (XRD), X-ray fluorescence (XRF), EDX, field emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM). Paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…It was found that the film of substrate thickness varies based upon the nature of the substrate, the fixed parameters structural like crystal pore, internal pressure, constant lattice and optical properties of composite (PbS) have also been affected using the chemical nature of the substrate It was observed from the UV spectrum that the Absorbance edge changed with the lower wavelength in the deposited films. The optical properties show that lead sulfide structure depoted on aluminium at the substrate glass of concentration (0.05M) is more transparent than the film on the glass substrate of (0.2M) due to effect on the morphological properties of the deposited substrate , these results are in agreement with [27,50,51]. It can be seen the improvement of the physics properties of thin films via choosing the appropriate substrate.…”
Section: Optical Propertiessupporting
confidence: 84%
See 1 more Smart Citation
“…It was found that the film of substrate thickness varies based upon the nature of the substrate, the fixed parameters structural like crystal pore, internal pressure, constant lattice and optical properties of composite (PbS) have also been affected using the chemical nature of the substrate It was observed from the UV spectrum that the Absorbance edge changed with the lower wavelength in the deposited films. The optical properties show that lead sulfide structure depoted on aluminium at the substrate glass of concentration (0.05M) is more transparent than the film on the glass substrate of (0.2M) due to effect on the morphological properties of the deposited substrate , these results are in agreement with [27,50,51]. It can be seen the improvement of the physics properties of thin films via choosing the appropriate substrate.…”
Section: Optical Propertiessupporting
confidence: 84%
“…*Corresponding author at: Physics Department, College of Education for Pure Science, Mosul University, Iraq; 0000;Tel:+964 -0000 -0000 -0000 https://orcid.org/ ORCID: E-mail address: ghazwan39@uomosul.edu.iq Lead sulfide (PbS) thin film has several practical applications such as infrared detectors [8,9,10], transistors, solar cells and biosensors [11,12,13] solar absorbers [14], photographs [15], telecommunications [16], LED devices [17], photonic switches [18,19] diode lasers [20,21] temperature and humidity sensors and coatings decorative, solar control [22,23,24] and quantum dot applications. Lead sulfide (PbS) thin film can be prepared in several ways such as successive ion layer absorbance [25], chemical deposition [26], spray method [27], galvanic method [28] atomic layer deposition [29] pulsed electrodeposition [30,31] vacuum evaporation [32] chemical vapor deposition [33,34] pulsed laser ablation [35] molecular beam filling [36] and microwave heating [37] in addition to the gelatin method [38]. Chemical Deposition has been widely useful for deposition because the technique is considered one of the most advantageous methods such as lower working temperatures, lower cost and easy deals of large size compared to other chemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…where Eu is the Urbach energy, which describes the breadth of the localised states in the band gap, and α o is a constant. In terms of absorption, the above equation can be expressed as (8) [63][64][65][66][67].…”
Section: Resultsmentioning
confidence: 99%